Peran Orang Tua dalam Mendukung Pendidikan Anak di MI Miftahul Huda Desa Sindangheula kecamatan Pabuaran kota serang : Penelitian - Nia Sundari; Ardiyanti Safitri; Alya Zalfa Zahidah; Agus Rohman; Muhammad Fajrul Falah; Mohammad Imam Kamaluddin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Education has a very broad meaning but in general it can be defined as a development process in various aspects such as knowledge, skills, attitudes, and values. Education is not only seen from an academic perspective but also includes broader aspects. Education is not only obtained in formal schools but families also play an important role in providing education to children. Education at the elementary school level is the main foundation for a child's academic and social growth because at this stage it is very important for character formation and academic development and parental involvement is the first educational environment for children. Parents have an important role and great responsibility in introducing education to children and parents who actively participate tend to create a positive learning atmosphere that can increase children's interest and self-confidence. This study aims to determine the role of parents in supporting children's education at the elementary school level at MI Miftahul Huda, Sindangheula Village. The method used in this study is the technique of data collection through observation, interviews, and documentation. The results of the study indicate that parents have an important role in supporting children's education, both through providing learning motivation, attention to school activities, and children's educational needs. However, in its implementation there are still several obstacles such as limited parental time and family economic conditions. With good parental involvement, the child's education process can run more optimally and help improve the child's academic and character development.